Dynamic changes in forest cover and human activities during the Holocene on the northeast Tibetan plateau - Wende, Zhuoma; Hou, Guangliang; Chen, Hongming; Jin, Sunmei; Zhuoma, Lancuo (Frontiers in Earth Science, 2023)
Human activities have a strong influence on the present day environment of the Tibetan Plateau, especially in the northeastern area. The questions of when and to what extent humans began to utilize the plateau environment have been long investigated, but there are still gaps in our understanding, such as the relationship between forest dynamics and anthropogenic activities. Here, we simulate the potential Holocene geographical distribution of the three dominant coniferous tree species in the Northeast Tibetan Plateau in response to climate/environment and analyze pollen records and multi-proxies for anthropogenic activities to explore human impact on natural forest dynamics. Simulation results show marked expansion of Picea and Pinus coniferous forests in the Early Holocene (11.5–8.3 ka BP), continuing into the Mid Holocene (8.3–4.0 ka BP). However, there was a slight contraction of forest in the Late Holocene (4.0–2.6 ka BP) in the western part of the region, and near disappearance in the eastern Qaidam Basin, although both Pinus and Picea slightly increased in Hehuang Valley. Pollen analysis confirms the patterns, with an increase in arboreal pollen mainly comprising Pinus and Picea from Early to Early Mid Holocene (11.5–5.3 ka BP), followed by a decrease. Proxies of anthropogenic activities, including carbon concentration, archeological sites, and, synanthropic plants, increased significantly after 5.3 ka BP, with archeological evidence for intensive exploitation of forest and turnover of natural vegetation. We argue that forest retreat at 5.3–4.0 ka BP was due to the expansion of cropland and increasing demand for wood. Significant coniferous forest retreat and degradation from 4.0–2.6 ka BP, with forest succession in Hehuang Valley, was driven by the booming population, extensive grazing, and forest exploitation; the drying cooling climate may have aggravated the pace of deforestation at higher elevations. This study presents new insights into the deforestation on the Northeast Tibetan Plateau in the Holocene.